2021
DOI: 10.35848/1347-4065/ac1985
|View full text |Cite
|
Sign up to set email alerts
|

Verification of inactivation effect of deep-ultraviolet LEDs on bacteria and viruses, and consideration of effective irradiation methods

Abstract: With the widespread of the novel coronavirus (SARS-CoV-2), the inactivation of bacteria and viruses using ultraviolet (UV) light has been reevaluated. However, there are many applications where the safety to the human body itself and inactivation effect itself are questioned, and there is a movement to review the UV-C guidelines (Global Lighting Association, Position Statement on Germicidal UV-C Irradiation UV-C SAFETY GUIDELINES, 2020). Since the Minamata Convention on Mercurybans the production of mercury in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The SLR's results demonstrate a concentration of studies [3,8,17,[21][22][23][28][29][30][31][32][33][34][35][36][37][38][39][40] in this scientific field. Of these studies, all found some level of decontamination effectiveness.…”
Section: Human Healthmentioning
confidence: 76%
See 4 more Smart Citations
“…The SLR's results demonstrate a concentration of studies [3,8,17,[21][22][23][28][29][30][31][32][33][34][35][36][37][38][39][40] in this scientific field. Of these studies, all found some level of decontamination effectiveness.…”
Section: Human Healthmentioning
confidence: 76%
“…In terms of disinfection (at least three log-reduction), we have seven studies [3,24,[33][34][35][36][37][38] indicating it. Meanwhile, ten studies [8,17,21,23,[28][29][30][31][32]39] indicate elimination of biological indicators (sterilization) or growth inhibition. In terms of lower levels of decontamination effectiveness, only one study [22] discussed it.…”
Section: Human Healthmentioning
confidence: 99%
See 3 more Smart Citations